2015
DOI: 10.1039/c4dt03477e
|View full text |Cite
|
Sign up to set email alerts
|

Solid-phase cyclopalladation in S,C,S′-pincer systems: rising alternative for synthesis in solution

Abstract: In pursuit of a new and simple approach to complex organometallic systems, the possibility of formation of a palladium-carbon bond in the solid state via direct cyclopalladation has been studied toward several S,C,S'-pincer ligands with thione sulfur donors of different nature. It is found that mixtures of the ligand and PdCl2(NCPh)2 obtained by the manual grinding of reactants in a mortar efficiently undergo solid-phase cyclometalation upon heating in open test tubes without the addition of a solvent to affor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Recently we have shown that simple heating of homogenized mixtures of a pincer‐type ligand and appropriate Pd(II) precursor, obtained by grinding of the reactants in a mortar, can become a powerful alternative to conventional synthesis of complex organometallic systems in solution . The suggested solid‐phase methodology appeared to be efficient for production of several series of C‐metallated pincer complexes combining thiophosphoryl donor groups with ancillary benzothiazole (compounds XVII – XIX ; Scheme ),[10b] thioamide (compounds XX , XXI ) and thiophosphorylamino ( XXII ) moieties [10a]. In the case of the highly reactive hybrid bis(thioamide) derivative, the formation of pincer complex XXIII was observed even at room temperature [10a].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently we have shown that simple heating of homogenized mixtures of a pincer‐type ligand and appropriate Pd(II) precursor, obtained by grinding of the reactants in a mortar, can become a powerful alternative to conventional synthesis of complex organometallic systems in solution . The suggested solid‐phase methodology appeared to be efficient for production of several series of C‐metallated pincer complexes combining thiophosphoryl donor groups with ancillary benzothiazole (compounds XVII – XIX ; Scheme ),[10b] thioamide (compounds XX , XXI ) and thiophosphorylamino ( XXII ) moieties [10a]. In the case of the highly reactive hybrid bis(thioamide) derivative, the formation of pincer complex XXIII was observed even at room temperature [10a].…”
Section: Resultsmentioning
confidence: 99%
“…The suggested solid‐phase methodology appeared to be efficient for production of several series of C‐metallated pincer complexes combining thiophosphoryl donor groups with ancillary benzothiazole (compounds XVII – XIX ; Scheme ),[10b] thioamide (compounds XX , XXI ) and thiophosphorylamino ( XXII ) moieties [10a]. In the case of the highly reactive hybrid bis(thioamide) derivative, the formation of pincer complex XXIII was observed even at room temperature [10a]. Not long ago the synthesis of an organometallic Pd(II) pincer complex XXIV was accomplished for the first time via CH bond activation of a bis(thiocarbamate) ligand with PdCl 2 (NCPh) 2 under mechanochemical conditions both by grinding of the reactants in a mortar and in a vibration ball mill at gram scale .…”
Section: Resultsmentioning
confidence: 99%
“…These reactions appeared to be the first examples of solid-phase synthesis of pincer complexes. Recently, the solid-phase strategy has been successfully used for synthesis of S,C,S 0 -pincer systems with different thione sulfur donors [99].…”
Section: Hybrid Pincer Compounds With Thione Sulfur Donorsmentioning
confidence: 99%
“…Extensive studies have been carried out on several pincer ligands with various combinations of C, N, S and P donors and related palladium/platinum complexes have been investigated for their photophysical and catalytic properties [7][8][9][10][11][12]. Amongst the well-known pincer complexes, the thioamide based ligands with SCS type are relatively less explored compared to the others [13,14]. Therefore, in order to examine the binding properties and associated photophysical and catalytic properties of these complexes, one of the methyl groups of each side of N,N,N',N'-tertamethylbenzene 1,3-dicarbothioamide are replaced by bulky tert-butyl group and another by hydrogen atom and employed for the complexation with Pd(II).…”
Section: Introductionmentioning
confidence: 99%